The normal response to prolonged passive head up tilt testing. Issue 5 (1st November 2000) - Petersen, M E V; Williams, T R; Gordon, C; Chamberlain-Webber, R; Sutton, R
Abstract : OBJECTIVE: To define the responses to head up tilt in a large group of normal adult subjects using the most widely employed protocol for tilt testing. METHODS: 127 normal subjects aged 19–88 years (mean (SD), 49 (20) years) without a previous history of syncope underwent tilt testing at 60° for 45 minutes or until syncope intervened. Blood pressure monitoring was performed with digital photoplethysmography, providing continuous, non-invasive, beat to beat heart rate and pressure measurements. RESULTS: 13% of subjects developed vasovagal syncope after a mean (SD) tilt time of 31.7 (12.4) minutes (range 8.5–44.9 minutes). Severe cardioinhibition during syncope was observed less often than is reported in patients investigated for syncope. There were no differences in the age or sex distributions of subjects with positive or negative outcomes, or in the proportions with cardioinhibitory and vasodepressor vasovagal syncope compared with previously reported patient populations. Subjects with negative outcomes showed age related differences in heart rate and blood pressure behaviour throughout tilt. CONCLUSIONS: False positive results with tilting appear to be common. This has important implications for the use of diagnostic tilt testing. The magnitude of the heart rate and blood pressure changes observed during negative tilts largely invalidates previously suggested criteria for abnormal non-syncopal outcomes.